La Cour suprême des États-Unis dans le débat sur la séparation de l’Église et de l’État : les arrêts McCreary v. ACLU of Kentucky et Van Orden v. Perry du 27 juin 2005 - Frédéric Heurtebize (Revue LISA)
This article discusses two US Supreme Court rulings issued on June 27, 2005, both dealing with the separation of Church and State. The Court was called to rule on whether the display of the Ten Commandments on public grounds violated the “establishment clause”. Beyond the purely legal question, the issue at hand tests some of America’s national foundations, i.e. its Constitution and its religious tradition. That the Supreme Court gave two seemingly contradictory decisions, and thus failed to “clarify the law”, by publishing two different decisions on such similar cases highlights that the issue remains a constitutionally delicate one. This study will seek to examine the arguments and ideological positions within the Court that led to this split ruling which will set an unclear legal precedent for the future.